On Structural Theories of International Relations: Examining Waltzian Structural Realism And Wallerstein’s World System Theory - Winner Agung Pribadi (Jurnal Hubungan Internasional, 2013)
This article attempts to look at two currents of thought which both have influences on International Relations study, which is structural realism that proposed by Kenneth Waltz and ideas of the world system from Immanuel Wallerstein. In both perspectives, the patterns of International Relations is presuppose the existence of structure determination and large system which surrounding actor or agent whose the presence is quite important in current International Relations. Through both of critical reviews which are utilizing the constructivist study, both structural realism ideas and world system ideas were neglected the role of agents that have a decisive role in International Relations. The neglect of the agent roles made both ideas are reductionist and tend to attempt global structure as an unit of analysis which deterministic.